Mathematical sciences in the karma antiquity - Jain, Laxmi Chandra (Gulab Rani Karma Science Museum and Shri Brahmi Sundari Prasthashram Samiti, 2008)
Includes text of Gommaṭasāra Jīva-Kāṇḍa in Prakrit with English and Hindi translation